2005
DOI: 10.1002/anie.200501491
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bonded Supramolecular Assemblies as Robust Templates in the Synthesis of Large Metal‐Coordinated Capsules

Abstract: Uncommon water chain: A large neutral hexameric coordination cage [Ga12(H2O)24(C40H42O12)6⊂(acetone)8(H2O)6] is assembled from six pyrogallol[4]arene ligands and twelve GaIII ions. Found within the capsule structure are two pseudo‐linear hydrogen‐bonded water (H2O)5 chains (see picture, Ga gold, O red).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 33 publications
1
58
0
Order By: Relevance
“…From the work reviewed in this article, we have also shown that they are also useful templates for metal-organic analogues [116,[118][119][120][121]124,127]. The remarkable replacement of 48 hydrogen atoms in the hydrogen-bonded 'seam' with 24 copper Fig.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 87%
See 2 more Smart Citations
“…From the work reviewed in this article, we have also shown that they are also useful templates for metal-organic analogues [116,[118][119][120][121]124,127]. The remarkable replacement of 48 hydrogen atoms in the hydrogen-bonded 'seam' with 24 copper Fig.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 87%
“…By exchanging copper(II) nitrate for gallium(III) nitrate in an acetone/water solvent system containing PgC 3 , diffraction quality colourless single crystals form over a number of hours [119]. Structural analysis of this material afforded a metal-organic capsule composed of six PgC 3 molecules and 12 gallium centres that has a distorted 'rugby-ball' like shape which is markedly different to the spherical type nano-capsules described in Section 3.1 (Fig.…”
Section: Gallium-based Metal-organic Pyrogallol[4]arene Nano-capsulesmentioning
confidence: 92%
See 1 more Smart Citation
“…S4). Together with these, one of possible multi-membered arrays assembled between DHBO and Ga 3 þ ions was illustrated in Scheme 1, where Ga 3 þ functions as quadridentate ligand like literature reported (McKinlay et al, 2005).…”
Section: Spectra Response Of Dhbo Upon Addition Of Ga 3 þ Ionsmentioning
confidence: 80%
“…The turn-on fluorescence signal can effectively discriminate ATP from ADP and adenosine 5′-monophosphate (AMP). Ga 3 þ ions were found to easily coordinate with oxygen atoms of hydroxyphenyl segments (Hastings et al, 2014;McKinlay et al, 2005McKinlay et al, , 2006. DHBO ligand is a typical fluorophore known for its excited state intramolecular proton transfer (ESIPT) characteristic (Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%